Socio-Economic Vulnerability to Potential Flood in Tamakoshi River in Nepal - Sigdel, Shalik Ram (Himalayan Review, 2024)
Tamakoshi, a transboundary river flowing from Tibet, China to Nepal has experienced several disastrous flash floods resulting in the loss of lives, infrastructures, settlements, lands, and other assets. Many households, populations, and public and private properties such as houses, land, roads, bridges, etc. are likely to be affected by the potential flash floods. This study discusses the occurrence of flash floods, losses and damages from such floods in the past, and socio-economic vulnerability to potential flash floods. It further discusses the preparedness and response activities and identifies the measures for flood risk reduction. The methods adopted for data collection included observation, household surveys, and focus group discussions. The villages selected for detailed study are Gongarkhola, Jagat, Jamune, Bhorle, and Sigati bazaar, identified as the most vulnerable settlements along the Tama Koshi River. It is found that flash floods and high-intensity precipitation occur frequently in the study area resulting in loss of life and properties, and people and properties are exposed to the potential flash floods. Local people are still feeling vulnerable to such flash floods. The government authorities alone are not able to achieve greater success in carrying out preparedness and response activities for flood risk reduction without the active involvement and participation of the vulnerable communities. Development and effective implementation of land-use guidelines and building codes, watershed management, early warning systems, and networking among the people residing across the river are some of the activities identified to reduce flood risk. Although people have a good understanding and knowledge about floods and their occurrences, they pay less attention to preparedness and mitigation. It is also concluded that structural measures alone are not sufficient and effective enough for flood risk reduction